Proposed enhanced link failure rerouting mechanism for software-defined exchange point - Abdijalil Abdullahi; Selvakumar Manickam; Shankar Karuppayah; Mahmood A. Al-Shareeda (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Internet eXchange point (IXP) is a way to optimize network bandwidth. It enables a platform in the different providers like internet service providers (ISPs) and content delivery providers (CDNs) to share their traffic through a common point. A software defined exchange point (SDX) is an IXP comprising of a programmable deployed software defined network (SDN) switching fabric to enhance the management of their services, but they met the performance issues. The previous studies proposed various mechanisms and frameworks that tackled with these issues, but they don’t overcome overall challenges like link failure recovery for multi-hop-based SDX particularly packet processing delay and switch memory overhead. To cope with these issues, this paper proposed an enhanced link failure rerouting (ELFR) mechanism for multi-hop-based SDX. The objective of the proposed ELFR mechanism is to reduce the delay of packet processing to recover the link failure quickly and improve the path computation while ensuring the switch storage overhead. The present paper is an effort to retrospect and analyze the critical review of existing work for SDX. Furthermore, this paper provides a background of SDX, its components and its applications. Finally, this paper presents and compares the expected results of ELFR mechanism and related work.